PURULENT-NECROTIC FORMS OF DIABETIC FOOT SYNDROME IN PATIENTS WITH CHRONIC RENAL FAILURE - Saitov, D.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Purulent-necrotic lesions in diabetic foot syndrome remain one of the most difficult clinical problems in patients with a combined course of diabetes mellitus and chronic renal failure. In the conditions of uremia and impaired tissue metabolism, infectious and necrotic processes on the lower extremities are especially severe, often requiring urgent surgical interventions. The present study is aimed at a comparative analysis of two categories of patients: patients with end-stage chronic renal disease who are on programmatic hemodialysis, and patients with chronic renal failure who receive only conservative therapy (diuretics and metabolic correction). A total of 28 patients with purulent-necrotic forms of diabetic foot syndrome were included in the study, of whom 14 were on hemodialysis and 14 were without dialysis. Clinical and laboratory parameters, the dynamics of the purulent process, the applied antibacterial therapy regimens, the volume and timing of surgical interventions, as well as treatment outcomes were analyzed. It has been established that patients on hemodialysis are characterized by a more pronounced systemic inflammatory reaction, a high frequency of the need for amputations, and a long period of re-epithelialization. At the same time, in patients with chronic renal failure without dialysis, conservative approaches are more effective with a lower frequency of severe surgical interventions. The data obtained emphasize the need for a differentiated therapeutic approach, taking into account dialysis status, as a key factor in the prognosis and tactics in the treatment of purulent-necrotic forms of diabetic foot syndrome.